Modulation of interfacial charge dynamics of semiconductor heterostructures for advanced photocatalytic applications - Tsao, Chun-Wen; Fang, Mei-Jing; Hsu, Yung-Jung (Coordination chemistry reviews, 2021)
[Display omitted] •Strategies to adjust charge dynamics of semiconductor heterostructures are reviewed.•Precise manipulation of charge transfer dynamics is still a grand challenge.•Insights into future advancement of photocatalysis technology are summarized. As a topic of intensive research interest for decades, photocatalysis using semiconductor heterostructures holds the potential to satisfy global energy demand, reduce greenhouse effect and accomplish environmental remediation. This burgeoning technology has quickly become a high-profile emerging scientific and technological field, providing a solution to achieving sustainable development of renewables. However, critical challenges, such as inadequate solar photons absorption, mediocre charge transfer dynamics, poor surface reaction kinetics and lack of long-term stability, have hindered the widespread deployment of semiconductor photocatalysts. Interfacial charge dynamics is particularly relevant to the utility of photocatalysis because it dictates charge transfer and carrier utilization, the two complicated yet key processes involved in the photocatalytic reactions. The means to modulating charge dynamics and even manipulating carrier behavior may pave a new avenue for intelligent design of versatile photocatalysts for advanced applications. This review introduces the recent development on conceptual strategies and experimental approaches that can be exploited to modulating charge dynamics of semiconductor heterostructures for maximizing carrier utilization efficiency. New insights into the future advancement of photocatalysis technology based on the adoption of the proposed tactics are also discussed and summarized.